2015
DOI: 10.1093/mnras/stv2437
|View full text |Cite
|
Sign up to set email alerts
|

The physics of water masers observable with ALMA and SOFIA: model predictions for evolved stars

Abstract: We present the results of models that were designed to study all possible water maser transitions in the frequency range 0-1.91 THz, with particular emphasis on maser transitions that may be generated in evolved-star envelopes and observed with the ALMA and SOFIA telescopes. We used tens of thousands of radiative transfer models of both spin species of H 2 O, spanning a considerable parameter space in number density, kinetic temperature and dust temperature. Results, in the form of maser optical depths, have b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 104 publications
(139 reference statements)
3
56
0
Order By: Relevance
“…About 130 of the detections are associated with AGNs, where they are called megamasers because of their large apparent luminosities. The physical conditions that give rise to maser activity at 22 GHz are also compatible with masing in other transitions of the H 2 O molecule, many of which fall in the submillimeter wavelength band (Neufeld & Melnick 1991;Gray et al 2016). Humphreys et al (2005) presented the first observations of H 2 O megamaser emission in a transition other than 22 GHz, detecting maser emission at 183 GHz and (tentatively) 439 GHz toward the galaxy NGC 3079.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…About 130 of the detections are associated with AGNs, where they are called megamasers because of their large apparent luminosities. The physical conditions that give rise to maser activity at 22 GHz are also compatible with masing in other transitions of the H 2 O molecule, many of which fall in the submillimeter wavelength band (Neufeld & Melnick 1991;Gray et al 2016). Humphreys et al (2005) presented the first observations of H 2 O megamaser emission in a transition other than 22 GHz, detecting maser emission at 183 GHz and (tentatively) 439 GHz toward the galaxy NGC 3079.…”
Section: Introductionmentioning
confidence: 68%
“…This is to be expected from consideration of the physical conditions required for strong maser activity in these transitions. Gray et al (2016) performed a thorough exploration of the relevant parameter space (i.e., gas density, kinetic temperature, and dust temperature) and found that the 321 GHz transition shares an optimal gas density ( » n 10 H 9 2 cm −3 ) and collisional pumping scheme (i.e., low dust temperature) with the 22 GHz transition, although it prefers a somewhat larger kinetic temperature of » T 1500…”
Section: Ghz H 2 O Masers In Circinusmentioning
confidence: 99%
“…The pumping of the H 2 O maser transitions that trace highvelocity molecular outflows is thought to be dominated by shocks with neutral molecular gas (Hollenbach et al 2013;Gray et al 2016). The pumping mechanism of the H 2 O transitions is very sensitive to changes of the collisional rates, and requires particular conditions of the density and kinetic temperature of the gas (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…These temperatures and densities are at the bottom of the range of conditions water masers can be found in. They can be found under a wide range of conditions, but they most favour temperatures of ∼800 K and number densities of 10 15 m −3 (Gray et al 2016).…”
Section: Introductionmentioning
confidence: 99%